Communication competence of Indonesian workers in intercultural interaction in Munich and Canberra - Aang Koswara; Syauqy Lukman (Jurnal Kajian Komunikasi, 2022)
The discourse of intercultural communication competence is increasingly important in the globalized world. However, there need to be more studies reported on the communication competence of Indonesian workers in intercultural interaction, particularly in the host country Germany and Australia. This study investigates communication competence in the intercultural interaction of Indonesian workers in two cities, Munich and Canberra. It focuses on intercultural challenges encountered by Indonesian workers working at different corporations and organizations in Munich and Canberra. Using qualitative methods, we examine Indonesian workers' intercultural awareness, sensitivity, and language competence in the host cities. This ethnographic study is based on interviews and informal conversations with Indonesian workers in Munich and Canberra and observations through the engagement of the researchers in the various Indonesian Diaspora community in the two cities. Based on thematic analysis, two empirical findings are essential to everyday intercultural interaction. First, intercultural awareness and sensitivity explain the knowledge and experiences of Indonesian workers on local rules and regulations, culture, and history of the host cities. Second, language competence describes the ability of Indonesian workers to understand the accents and dialects (German Bavaria and English Australian) and to overcome language barriers in everyday work and community life. The study concludes that participants have different experiences implementing communication competence in everyday interaction. It depends on the intercultural interaction intensity of Indonesian workers with their colleagues and the local community.